WEIGHT MANAGEMENT: NEED ASSESSMENT FOR HEALTH EDUCATIONAL MODULE DEVELOPMENT AMONG PRIMARY SCHOOL CHILDREN - Norimah Said; Norazmir Md Nor; Siti Khuzaimah Ahmad Sharoni; Siti Sabariah Buhari; Nurul Fadly Habidin (Malaysian Journal of Public Health Medicine, 2020)
The prevalence of overweight and obesity among school children are increasing in developing countries, including Malaysia. The aim of this study was carried out the need assessment and to determine the nutritional knowledge, attitude, and physical activity among primary school children for the purpose of health education module development on childhood weight management among primary school children. This study was employed cross-sectional design with a probability of 202 school children aged ten years old. The result shows that majority of primary school children choose food that high in carbohydrate, sodium, and saturated fat. Thus, reflect to the lack of nutrition knowledge. Meanwhile, for the lowest choices were sugar intake and low-fat dairy product. The highest mean for nutritional attitude is primary school children chose to drink 100% fruit juice (mean=81 ± 0.97), and the lowest mean was eating wheat bread (mean=2.25 ± 1.16). The highest mean for sedentary activity was watching the television show during weekdays (mean 4.02 ± 1.17). The result shows the children need education on the nutritional fact in their food like carbohydrate, sodium and saturated fat, physical activity, and information to avoid a sedentary lifestyle.